Pelaksanaan Penegakan Disiplin Pegawai Kontrak di Kantor Dewan Perwakilan Rakyat Daerah (DPRD) Kabupaten Tabanan - I Putu Dion Mahardika; Ida Ayu Putu Widiati; Luh Putu Suryani (Jurnal Interpretasi Hukum, 2022)
Contract Employees have an important role to achieve the success of the government. However, in reality there are still many shortcomings made by Contract Employees, especially the implementation of discipline. Discipline is an important factor to achieve the success of an organization. There are two main problems, namely how to implement contract employee discipline and how to enforce contract employee discipline at the office of the Regional People's Representative Council (DPRD). This study uses the type of empirical legal research taken by means of interviews, observations and literature research. The results of this study are, the implementation of contract employee discipline in the Tabanan Regency DPRD Office has been carried out smoothly. There are shortcomings in the enforcement of contract employee discipline. The factor that hinders the implementation of contract employee discipline is the HR factor. Efforts in enforcing the discipline of counter-employees at the Tabanan DPRD office are prevention and prosecution efforts.